An approach to measuring language-specific brain function in developmental language disorder - Caroline Larson; Jason C. Crutcher; Hannah R. Thomas; Michael C. Stevens (Acta Psychologica, 2025)
Purpose: Evidence characterizing brain function in developmental language disorder (DLD) is limited because measured brain function may reflect individual variability in task performance and error processing. This methodological study began characterizing language-specific brain function by administering the adaptive semantic matching paradigm during functional magnetic resonance imaging (fMRI) to individuals with DLD and by using a Bayesian analytical approach appropriate for small clinical samples. Methods and results: The adaptive semantic matching paradigm involved word-similarity judgements (e.g., age-night) and perceptual-similarity judgements of symbol strings (e.g., τουχφ-τουχε; i.e., control condition) during fMRI scanning. The adaptive component involved increases or decreases in task difficulty depending on in-the-moment individual participant accuracy (2-up-1-down adaptive weighted staircase, converges >80 % accuracy); controlling for individual variability in task performance. Bayesian analyses involved model comparison and second-level generalized linear models. Participants were adolescents with DLD (n = 5) and neurotypical controls (n = 12). Analyses indicated group differences in activation for right hemisphere frontal, temporal, and semantic language homologue networks, and no reliable differences in left hemisphere language networks or in lateralization. Conclusions and contributions: The methodological contributions of the current study were the adaptive paradigm that elicits language-specific function and an analytical approach that is reliable for small, heterogeneous samples. These methods may differentiate whether variability in left hemisphere and lateralization patterns reflect between-study differences on in-scanner task performance versus the heterogeneous DLD profile. Future research guided by these methods and findings may reveal new insights that inform theoretical and clinical models of this highly prevalent neurodevelopmental condition.